2009
DOI: 10.1002/ps.1773
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of QoI‐resistant field isolates of Botrytis cinerea from citrus and strawberry

Abstract: The conventional RFLP and sequence analyses of PCR-amplified cytochrome b gene are insufficient for molecular identification of QoI resistance in B. cinerea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 25 publications
4
70
2
3
Order By: Relevance
“…Previous studies indicated that alternative oxidase (AOX) is one way to decrease the damage of strobilurin fungicides in certain fungal pathogens. 33,41,42) Furthermore, the culture medium added with an AOX inhibitor of salicylhydroxamic acid (SHAM) or n-propyl gallate (PG) could increase the inhibitory activity of strobilurins against fungal pathogens. 33,41,42) In this study, the M. oryzae isolates showed variable sensitivity to azoxystrobin and kresoxim-methyl, and the different sensitivities might be caused by the level of AOX activity in each M. oryzae isolate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that alternative oxidase (AOX) is one way to decrease the damage of strobilurin fungicides in certain fungal pathogens. 33,41,42) Furthermore, the culture medium added with an AOX inhibitor of salicylhydroxamic acid (SHAM) or n-propyl gallate (PG) could increase the inhibitory activity of strobilurins against fungal pathogens. 33,41,42) In this study, the M. oryzae isolates showed variable sensitivity to azoxystrobin and kresoxim-methyl, and the different sensitivities might be caused by the level of AOX activity in each M. oryzae isolate.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transports are also closely related to multiple drug resistances. 21,42) Thus, the AOX and ABC transports might play an important role in reducing the damage of strobilurin fungicides in the less sensitive M. oryzae isolates from Taiwan. It warrants further investigation to confirm the mechanism of the resistance to strobilurins.…”
Section: Discussionmentioning
confidence: 99%
“…Specific resistance has been described e.g. to benzimidazoles such as benomyl, thiophanate-methyl and carbendazim (Yarden & Katan, 1993;Yourman & Jeffers, 1999), dicarboximides such as iprodione and vinclozolin (Northover & Matteoni, 1986;Yourman & Jeffers, 1999), QoI fungicides (strobilurins; Bardas et al, 2010;Ishii et al, 2009), anilinopyrimidines such as cyprodinil and pyrimethanil (Chapeland et al, 1999;Myresiotis et al, 2007), carboxamides/SDHIs (boscalid; Leroux et al, 2010), and the hydroxyanilide compound fenhexamid (Fillinger et al, 2008;Ziogas et al, 2003). To the best of our knowledge, no reports of specific resistance to the phenylpyrrole compound fludioxonil have been published as yet.…”
Section: Fungicide Resistance In B Cinereamentioning
confidence: 99%
“…Yoshi-7, Yoshi-14 and Yoshi-20 were collected from citrus plants in Wakayama Prefecture, Japan. 11,12) M09149, M09152, M09161, M09163, M09182 and M09212 were collected from tomatoes in Mie Prefecture, Japan. The sensitive strains KU-26-1, KU-59 and KU-76, maintained in the Life Science Research Institute of Kumiai, were used as the standard.…”
Section: Reference Isolatesmentioning
confidence: 99%
“…11) These isolates change from glycine to alanine at position 143 (G143A) in the cytochrome b gene. 12) On the other hand, inhibitory effects of pyribencarb to cytochrome b enzyme on the transfer system of a QoI-resistant strain of B. cinerea were stronger than those of other QoI fungicides. 4) In other words, the binding site of pyribencarb to cytochrome b was assumed to be a little different from that of other QoI fungicides.…”
Section: Introductionmentioning
confidence: 97%